Long-term outcome of bone marrow transplantation in NIK deficiency: non-redundant role of non-canonical NF-κB signaling in thymic reconstitution and secondary lymphoid organ development - Köstel Bal, Sevgi; Haskoloğlu, Şule; Ransmayr, Bernhard; Sevinç, Selin; İslamoğlu, Candan and Baskın, Kübra and Deveci, Nazlı and Savaş, Berna and Fitoz, Suat and Küpesiz, Alphan and Kendirli, Tanıl and Boztug, Kaan and Doğu, Figen and İkincioğulları, Kamile Aydan (Frontiers in Immunology, 2025)
IntroductionBiallelic mutations in MAP3K14, encoding NF-κB-inducing kinase (NIK), disrupt non-canonical NF-κB signaling and lead to a rare inborn error of immunity marked by impaired lymphoid organ development, defective lymphocyte maturation, and susceptibility to recurrent infections. Hematopoietic stem cell transplantation (HSCT) has been considered a curative approach, yet its long-term efficacy remains unclear.MethodWe report long-term outcomes of two patients with genetically confirmed NIK deficiency who underwent HSCT.ResultsBoth patients achieved full donor chimerism and early T-cell reconstitution with normalized CD3+, CD4+, and CD8+ counts and naïve T-cell subsets. However, memory T-cell differentiation remained impaired, with persistently reduced central memory T cells and circulating T follicular helper cells. Immune dysregulation emerged years after HSCT, with one patient developing seropositive arthritis and the other exhibiting autoimmune hepatitis. Thymic dysfunction was suspected as an underlying contributor to impaired central tolerance in this pathology. Similarly, B-cell reconstitution was incomplete, characterized by persistent hypogammaglobulinemia and a marked deficiency in class-switched memory B cells, despite donor-derived chimerism. Lymphoscintigraphy confirmed absence of lymph nodes. Both patients suffered from recurrent, severe infections and ultimately died of infection-related complications. Our findings indicate that HSCT alone is insufficient to fully correct the immune disorder in MAP3K14 deficiency, likely due to non-hematopoietic defects in lymph node stromal structures and thymic central tolerance.DiscussionThese results highlight the importance of long-term immunologic monitoring, including assessments for immune dysregulation and anti-cytokine autoantibodies. Future therapies should consider adjunct strategies such as thymic regeneration or targeted immune modulation to address the underlying architectural defects in this disorder.